Allied health care in the early stages of the COVID-19 pandemic: A qualitative study on the perceptions of non-hospitalized patients and allied health professionals - Carla Agasi-Idenburg; Anja de Kruif; Amber Ronteltap; Sonja van Oers; Ton Satink; Marian de van der Schueren; Cindy Veenhof (PLoS ONE, 2026)
Purpose Worldwide, the COVID-19 pandemic disrupted access to primary care and rehabilitation services, leaving many non-hospitalized patients with persistent symptoms unsure where to seek support. Primary allied health care (pAHP) became an important source of guidance and rehabilitation in several countries. This qualitative study explored how pAHP was accessed, experienced, and delivered in the Netherlands during the early stages of the pandemic, focusing on non-hospitalized patients with lingering symptoms following SARS-CoV-2 infection and the allied health professionals who supported them. Methods A qualitative study was conducted in the Netherlands between January and May 2021. Semi-structured interviews were held with 11 non-hospitalized patients and 30 primary allied health care professionals across five disciplines. Participants reflected on their experiences with primary allied health care during the first year of the pandemic. Data were analyzed using inductive thematic analysis. Results Three main themes described this period: (1) navigating uncertainty in the absence of guidelines and knowledge about the disease; (2) adapting care, balancing treatment content and delivery; and (3) forging connections, including interprofessional collaboration and organization in primary care. Patients generally reported positive experiences and valued feeling heard and supported, while professionals described adaptive strategies and organizational challenges. Conclusions Primary allied healthcare played a valued and adaptive role for non-hospitalized patients during the early pandemic. These findings underscore the importance of acknowledging patients’ symptoms, strengthening interprofessional collaboration, and supporting flexible, evidence-informed care strategies to prepare primary care systems for future health crises.